Pengaruh Pertumbuhan Penjualan, Beban Operasional, Perputaran Kas, Pendapatan Operasional Terhadap Laba - Gultom, Gres Marta W.; Tania, Caroline (Universitas Gorontalo, 2023)
This research aims to prove and analyze the sales growth, operational expenses, cash turnover, and operating income's impact on profit in Consumer Goods Industry Companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2021. The data analysis model applied is multiple linear regression analysis. The research results, when tested simultaneously with an F-test, show that the variables of sales growth, operational expenses, cash turnover, and operating income have an impact on profit. The discussion results, when tested individually with a T-test, show that the variables of sales growth, operational expenses, cash turnover, and operating income do not have a partial and significant impact on profit.